Preparation And Properties Of Rubber Seed Kernel Powder/Recycled Polystyrene Composites - Hawarl, Akmal Afham (2014)
Recycled polystyrene (RPS)/rubber seed kernel powder (RSKP) composites at O, l, 3, 5, and 10 wt% of RSKP were prepared in an internal mixer at 180°C with 60 rpm of rotor speed for 8 minutes. Processing torque, tensile strength, elongation at break, Young's modulus and impact strength decreased with higher RSKP loadings, but water absorption increased. In comparison to virgin polystyrene (VPS)/RSKP, RPS/RSKP composites had lower processing torque, tensile strength, elongation at break, impact strength and water absorption. Maleic anhydride (MAH) incorporation into RPSIRSKP composites showed higher tensile strength, elongation at break, Young's modulus and impact strength as compared to RPSIRSKP composites. The presence of MAH increased the impact strength at l, 3, and 5 wt% of RSKP loadings. Modifying of RSKP filler with natural rubber latex improved tensile strength, elongation at break and impact strength for RPS/RSKP composites.